Ellen Smith-Dennis. 2020. A Grammar of Papapana. An Oceanic Language of Bougainville, Papua New Guinea (Pacific Linguistics 659). Boston–Berlin: De Gruyter Mouton. Pp. xxv + 532. - Majewicz, Alfred F. (Lingua Posnaniensis, 2022)
REVIEW: Ellen Smith-Dennis. 2020. A Grammar of Papapana. An Oceanic Language of Bougainville, Papua New Guinea (Pacific Linguistics 659). Boston–Berlin: De Gruyter Mouton. Pp. xxv + 532.